Characteristic of social attitudes of employees in the regional community - A. I. Nelgovsky (Вестник Северо-Кавказского федерального университета)
There is a social interpretation and operationalization of the concept “social attitude” offered. There is also an analysis of the empirical data obtained from an empirical study of the attitudes among contract labourers in the Stavropol Region.